MERFISHing for spatial context. Issue 7 (July 2015) - Shalek, Alex K.; Satija, Rahul
<x xml:space="preserve">Abstract</x> A new paper in Science by Zhuang and colleagues introduces multiplexed error-robust FISH (MERFISH). MERFISH extends single-molecule imaging techniques to profile the copy number and localization patterns of thousands of genes, representing a major advance for spatial transcriptomics, with exciting potential applications in immunology.